THREE PRIORITIES FOR THE FUTURE OF ISLAMIC RELIGIOUS EDUCATION FOLLOWING BEYZA BILGIN’S LINE OF THOUGHTS IN TEACHERS PROFESSIONAL LEARNING - Selçuk, Muallâ 1956- (2020)
Bu yazı Türkiye’de Din Eğitimi Bilimi’nin öncü ismi Prof. Dr. Beyza Bilgin’in düşünce dünyasından yola çıkarak, öğretmen yetiştirmede geleceğin din eğitimi için üç öncelikli yetkinlik alanı önermektedir. Bilgin’in Eğitim Bilimi ve Din Eğitimi kitabı bir taraftan ilgili disiplinlerle işbirliğini esas alan bütüncül bir din eğitimi yaklaşımı sunarken aynı zamanda bir eğitim teolojisi ihtiyacına işaret eder. Eser, her türlü din eğitimi faaliyeti için alanın özelliklerine uygun davranış geliştirme ve dini hükümleri pratikte değerlendirmenin bir yetkinlik olarak öğrenilmesi ihtiyacını teorik ve pratik açıdan gözler önüne serer. Gelenek kavramı bu nedenle din eğitimini güncel olanla ilişkilendirmek açısından kilit bir öneme sahiptir. Nakil ve ona bağlı bilgileri tanımak, onların gerçekte ne demek istediğini anlamak, Bilgin’e göre din eğitimi faaliyetinin temelidir ve ancak bu sayede vahyin etkili bir biçimde öğretimi mümkündür. Elinizdeki yazı, yazarın düşünce ağına takılan ve Bilgin’in din eğitimi felsefesi içerisinde oluşturduğu özgün fikirleriyle gösterdiği hedefleri anlama ve anlamlandırma denemesidir.
This essay presents three essential priorities for the future of Islamic religious education (IRE) inspired by Professor Beyza Bilgin’s vision. Professor Beyza Bilgin is the pioneer of the field and the founder of religious education in Turkish academia. In her well-known book Eğitim Bilimi ve Din Eğitimi (Education Science and Religious Education) Bilgin provides sets of assumptions and assertions to be used in interpreting and explaining the process of teaching and learning religion and helps us think about the nature of religious education in new ways. Bilgin sends an invitation to the educators of Islam to challenge established practices and ways of thinking and to suggest possibilities in an integrative way. Seeking integrity when it comes to teacher training in Bilgin’s perspective is a strong process in teacher’s own understanding to meet more effectively the needs of the today’s and tomorrow’s learners. According to Bilgin, the concept of tradition is basic in religious education. Giving meaning to isolated parts of the tradition, putting them in perspective, interpreting them, linking Islamic sciences up human sciences and illuminate the message in a revealing way seem to be her main considerations which indicate the ways to shape religious education as a discipline. Following Bilgin’s line of thoughts, this essay will try to define what aspects of teacher education accomplish the benefit of integration in constructing an Islamic worldview by naming three priorities in teachers’ qualifications as competencies.
Keywords: Anlama; Beyza Bilgin; Din Eğitimi; Gelenek; Religious Education; Teacher; Tradition; Understanding; Öğretmen